The Comparison between Exercise Therapy and Biofeedback Therapy in Facial Function and Quality Of Life of Bell’s palsy - Mirzakhani, Navid; Angooti Oshnari, Leila; Akbarzadeh Baghban, Alireza; Eliyspoor, Dariuosh; Javantash, Atiyeh; Kamalifar, Mahvash; Parsamanesh, Tayebeh (Journal of Clinical Physiotherapy Research, 2017)
Introduction: Bell’s palsy is the side effect of peripheral nerve palsy that causes low function of face and quality of life. This study was conducted to assess the effect of two different methods; exercise therapy and biofeedback therapy, accompanied with massage in two groups on facial function and quality of life of these patients. Materials and Methods: In this interventional research with before- after design, 20 patients with acute unilateral peripheral facial palsy participated in two separate programs. Function of face was measured by House Brackman and quality of life was evaluated by SF-36 questionnaire. In each group data were recorded before the intervention and 4 weeks (3 sessions per week) after it. Exercise therapy included receiving massage, doing patterns of Proprioceptive Neuromuscular Facilitation (PNF) and some exercises in front of mirror; besides, biofeedback therapy contained massage and muscular education by biofeedback set. After employing Kolmogorov-Simonov as a Test for normality, Independent T-test was utilized to compare means. Results: After one month doing two different programs in two exercise and biofeedback groups, remarkable increase of quality of life (P≤0.001) and also improvement of function of face (P=0.004) were noticed in each group, but there was not any significant difference between quality of life (P=0.07) and function of face (P=0.85) in two groups. Discussion: This study indicated that with regard to suffering paralysis in Bell’s palsy and its bad effects on patients’ quality of life, the use of both biofeedback and exercise therapies as treatment is effective. It seems that increasing awareness of patients and training early movements have important role in improvement improve. Key words: Bell’s Palsy, Biofeedback, Massage, Exercise Therapy, Facial Function, Quality of Life